The Life of the Virgin: Maximus the Confessor. by Stephen J. Shoemaker - Panagopoulos, Spyros P. (The journal of theological studies, 2013)
Since the 1980s the academic study of women has blossomed in many aspects: history, theology, feminism, archaeology, sociology, etc. It is obvious that the Marian studies could not remain unaffected. Martin Jugie, Michel van Esbroeck, Korneli Kekelidge, Antoine Wenger, Frédéric Manns, Brian Daley, Alice-Mary Talbot, Angeliki Laiou, Alexander Kazhdan, Stephen Shoemaker, Claudia Rapp, and many others have contributed to the study of the last days and the early cult of the Holy Virgin. The most significant publications include L. Brubaker and M. B. Cunningham (eds.), The Cult of the Mother of God in Byzantium (Ashgate, 2011), M. B. Cunningham, Wider than Heaven: Eighth-Century Homilies on the Mother of God (St.